THE â€œGreenâ€ TERM AND ACCOUNTING EDUCATION - Khairin, Fibriyani Nur; Sukoharsono, Eko Ganis; -, Roekhudin -; Hariadi, Bambang - (The International Journal of Accounting and Business Society, 2020)
AbstractPurpose â€“ This paper aims to uncover the meaning of "green" through the point of view of accounting educators.Design/methodology/approach â€“ Ecophenomenology is used as a methodology to uncover the meaning of â€œgreenâ€ by involving three professors from several universities in Indonesia who focus on sustainability and green accounting as informants.Findings â€“ This research shows that accounting educators provide a deeper meaning related to green, which in addition to considering the triple bottom line (3P) concept also includes values/beliefs as spiritual elements in it. "Green" is specifically interpreted as a process of harmony in life.Practical Implications â€“ Finding of this research contributes to construct green accounting educationâ€™s form that not only focuses on the concept of business with 3P aspects but there is a spiritual aspectalization, so that accountants resulting from such education have a holistic view of their environment.Originality/value â€“ Terminology in the field of green accounting is experiencing rapid development both in terms of meaning and new terms that emerge. Not much research has paid attention to the definition and meaning of the term yet, especially the term "green" itself. Whereas, the term and itâ€™s meaning might impact to the development of green accounting education.Keywords â€“ Accounting, Ecophenomenology, Education, Sustainability, TerminologyPaper Type â€“ Research Paper